2016
DOI: 10.1128/aac.01367-16
|View full text |Cite
|
Sign up to set email alerts
|

N -Desmethylclozapine, Fluoxetine, and Salmeterol Inhibit Postentry Stages of the Dengue Virus Life Cycle

Abstract: Around 10,000 people die each year due to severe dengue disease, and two-thirds of the world population lives in a region where dengue disease is endemic. There has been remarkable progress in dengue virus vaccine development; however, there are no licensed antivirals for dengue disease, and none appear to be in clinical trials. We took the approach of repositioning approved drugs for anti-dengue virus activity by screening a library of pharmacologically active compounds. We identified N-desmethylclozapine, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…We speculate that DDX3X may mediate anti-viral effects independent of IFN-β response by other stress response pathways. We have shown recently that drugs that induced autophagy acted as potent inhibitors of DENV replication (Medigeshi et al, 2016 ). Therefore, it would be interesting to investigate the role of DDX3X in autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that DDX3X may mediate anti-viral effects independent of IFN-β response by other stress response pathways. We have shown recently that drugs that induced autophagy acted as potent inhibitors of DENV replication (Medigeshi et al, 2016 ). Therefore, it would be interesting to investigate the role of DDX3X in autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…All the cell lines, virus strain used in this study and virus titering protocols have been described previously (Agrawal et al, 2013 ; Medigeshi et al, 2016 ). Huh-7, HEK293T, A549 cells were grown in Dulbecco's modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 1 mM L-glutamine, 100 units/ml penicillin-streptomycin-glutamine and non-essential amino acids at 37°C and 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…Caco-2, A549, Huh-7, BHK-21, C6/36, HEp-2, PS, and MA104 cells were cultured as described previously (15)(16)(17). Virus strains used in the study and infection procedures has been described before (15)(16)(17). DENV-2 New Guinea C strain was a kind gift from Dr. Navin Khanna.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…Most of the experiments have been performed in both the cell lines and we have obtained similar results. Plaque assay for DENV, JEV, and RV was set up in BHK-21, PS, and MA 104 cells respectively as described previously (15)(16)(17).…”
Section: Cells and Virusesmentioning
confidence: 99%
“…99) Lee et al evaluated the anti-DENV2 effect of a cocktail of aqueous extracts from four Phyllanthus spp., and found that that the cocktail altered the expression of 13 regulatory viral and host proteins that act on viral attachment, viral entry, polyprotein production, replication, assembly, and maturation. 100) The molecular mechanism and the effect on other serotypes were not reported.…”
Section: Inhibitors Targeting Host Proteinsmentioning
confidence: 99%